1998
DOI: 10.1021/ja972879x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regio- and Stereoselective [3+2] Cyclopentanone Annulation Using a 3-(Alkylthio)-2-siloxyallyl Cationic Species

Abstract: A new synthetic method for functionalized cyclopentanones was developed on the basis of a [3+2] cycloaddition reaction of a 1-(methylthio)-2-siloxyallyl cationic species and olefins. Allyl acetates 1a and 1b, which are the precursors of the allyl cationic species, are easily prepared in three or four steps from commercially available compounds. Under the influence of EtAlCl2 or AlCl3, 1a or 1b reacted with various kinds of olefins such as enol ethers, vinyl sulfides, styrenes, and trialkylolefins to afford the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…10 Although they are commonly utilized in (4+3) cycloadditions, Kuwajima demonstrated a highly regio- and stereoselective (3+2) cyclopentannulation by employing sulfur-substituted oxyallyl cations. 11,12 …”
Section: Heteroatom-substituted Oxyallyl Cationsmentioning
confidence: 99%
“…10 Although they are commonly utilized in (4+3) cycloadditions, Kuwajima demonstrated a highly regio- and stereoselective (3+2) cyclopentannulation by employing sulfur-substituted oxyallyl cations. 11,12 …”
Section: Heteroatom-substituted Oxyallyl Cationsmentioning
confidence: 99%
“…Among this group of compounds, highly functionalized cyclopentenes are particularly important targets 2. Various methods, such as transition‐metal catalyzed,3 anionic,4 cationic,5 and free‐radical‐mediated [3+2] cycloaddition6 have been investigated. In recent years, phosphine‐catalyzed [3+2] cycloaddition, developed by Lu and Zhang in 1995,7 has inspired fruitful discoveries, especially for preparing various carbocycles and heterocycles 8.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, one of the authors reported the regio-and stereoselective [3+2] cycloaddition reactions using allyl acetates 1a and 1b as a three-carbon unit (Scheme 2). 9 Under the influence of EtAlCl 2 , allyl acetate 1 reacted with alkene 2 to afford cyclopentanone 3 in good yield. In this reaction, the methylthio group of 1 plays an important role in stabilizing the allyl cation species A as well as controlling the regio selectivity of the cycloadducts.…”
Section: %mentioning
confidence: 99%